2018
DOI: 10.15419/bmrat.v5i8.467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of virulence genes in Klebsiella Pneumoniae clinical isolates from Kurdistan Province, Iran

Abstract: Introduction: The purpose of this study was to detect ybtS, entB, mrkD, magA, kfu, iutA, rmpA and K2 genes in extended-spectrum beta-lactamase (ESBL) - and non-ESBL producing Klebsiella pneumoniae. Methods: To this end, 70 K. pneumoniae isolates were selected from hospitals of Kurdistan Province, Iran. The ESBL phenotype was conducted utilizing the disc diffusion technique in accordance with CLSI procedures. Detection of virulence factor genes was performed by the PCR in the ESBL and non-ESBL isolates.&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
4
1
Order By: Relevance
“…They could not detect any virulence genes in 2Á7% of their isolates. The levels of virulence genes were comparable with previous works by different authors where a wide range of values was observed and reported (Jian- Li et al 2017;Shakib et al 2018;Ali and Al-kakei, 2019). However, the difference among the values could be due to different geographical location and sample size.…”
Section: Virulence Gene Profilingsupporting
confidence: 89%
“…They could not detect any virulence genes in 2Á7% of their isolates. The levels of virulence genes were comparable with previous works by different authors where a wide range of values was observed and reported (Jian- Li et al 2017;Shakib et al 2018;Ali and Al-kakei, 2019). However, the difference among the values could be due to different geographical location and sample size.…”
Section: Virulence Gene Profilingsupporting
confidence: 89%
“…The serotype k1,k3 , k5 and k20 genes were not detected in K. pneumonia isolates . Regarding serotype K2 gene, it was identified in 12.9 % isolates of our study but was not detected in study of Hamam et al [10] and Shakib et al [14] . However, it was reported in 6.7 % in the study of Chen et al [5] Serotype K54 detected in 37.8 % isolates of our study and 2.1 % in the isolates of study by Chen et al [5] .Capsule serotype k57 in 25.8 % isolates of our study, while in the study of Ssekatawa et al [18] there was no detection of K57 serotype gene.…”
Section: Detection Of Capsular Serotype Genes In Clinical Specimenscontrasting
confidence: 70%
“…pneumoniae isolated in the 1940s and 1950s prior to the widespread use of antibiotics [ 32 , 33 ], were compared to more recently isolated strains [ 34 ]. Wand, et al [ 32 ] and Shakib et al [ 35 ] both reported similar patterns in expression of virulence and resistance factors with differences between pre-antibiotic and more recent strains supporting the idea that important virulence and resistance factors that were infrequently expressed in pre-antibiotic era K . pneumoniae strains are now commonly expressed.…”
Section: Discussionmentioning
confidence: 92%